Religiusitas dan resiliensi santri selama pandemi COVID-19 - Isrida Yul Arifiana; Dyan Evita Santi; Fauzul Adim Ubaidillah (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
The Corona Virus Disease (COVID-19) pandemic impacts several aspects of the social life of students at Islamic Boarding Schools. Resilience is one of the psychological resources developed by individuals and communities to prevent the negative impact of the Corona Virus Disease (COVID-19) pandemic. This study aims to examine the relationship between religiosity and resilience. This research uses the quantitative correlational method. The participants of this study amounted to 216 students who were selected based on a simple random sampling technique. This study uses a resilience scale from Wagnild & Young to measure resilience, and the religiosity scale is based on the dimensions of Islamic worldview and religious personality from Krauss, Hamzah, Juhari, & Hamid. Analysis of this research data using regression analysis with the help of Jeffrey's Amazing Statistics Program (JASP). The results of this study indicate that religiosity has a positive and significant relationship with resilience. Suggestions from this study are that the results of this study can be used as a basis for developing student resilience. Further researchers are expected to examine other psychological resources to develop resilience during the COVID-19 pandemic.